Faire la preuve de l’urbanisme durable : Les enjeux de la régénération de l’île de Nantes - Pierre-Arnaud Barthel (Éditions en environnement VertigO, 2009)
Is the regeneration of urban and harbour brownfields a great opportunity for French decision-makers to show their know-how in urban planning towards a sustainable perspective? What are the challenges connected with their revitalization in an ecological and social perspective? To answer this questioning, we shall deliver here some learnings from the project of renewal of the Island of Nantes. This urban redevelopment is interesting because we can analyze, first of all, the effects of the "parachuting" of the label eco-district by the local elected representatives on this territory. Then, the challenges connected to the restoration of certain number of fallow lands of the island allow focusing on the choices in urban planning. Finally, the participations to European projects give the opportunity to the institutional to make of the island a territory of "demonstration". This priority given to the eco-technological proofs reveals, on the contrary, a weak political will to associate the inhabitants in order to implement the eco-district.